Organizational affiliation in the absence of financial allocations for members of the Iraqi Olympic sports federations - Latif Ali, Ali Abdul (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The purpose of this study was to analyze the organizational affiliation in the absence of financial allocations for members of the Iraqi Olympic sports federations. The study population consisted of all members of the administrative bodies of the Iraqi Olympic sports federations, who numbered 195 individuals. The participants completed a questionnaire of organizational affiliation, and the data were analyzed with SPSS. It was found that the arithmetic mean of the total score was 3.94 and the standard deviation was 0.54. This indicates that the degree of organizational affiliation in the absence of financial allocations for members of the Iraqi Olympic sports federations is high.